The Airbnb Story : How Three Ordinary Guys Disrupted an Industry, Made Billions... and Created Plenty of Controversy /? - Gallagher, Leigh
A thorough and objective profile of this groundbreaking and unusual company covers its founders, meteoric rise, nagging troubles, and global popularity